Attributes, Benefits and Attitudes: Construct of Zimbabwe Tourism Brand Association Amid Covid-19 Pandemic - Chigora, Farai; Katsande, Chipo (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
The study investigated the factors reflecting and building positive brand association for Zimbabwe tourism destination into the resurgent of COVID-19 pandemic. The focus was on three primary sources of brand association comprising attributes, benefits, and attitudes, which were then assessed to come with the most dominant element(s) for restoring a positive global image. A mixed sequential qualitative to quantitative research design was applied for the study. Qualitative research established sources for the brand association as themes that are acknowledged to be prevailing in Zimbabwe tourism destinations. This was achieved through in-depth interviews with participants who were purposively selected for the study. Further quantitative research was done to understand the most dominant factors for brand association and categorize them as attributes, benefits or attitudes. Results from qualitative research informed the themes for a brand association: perception by the origin of the tourist; references from others; the hospitality of tourism providers; media reports; existing natural resources; accessibility; cultural originality; government policies; and adventure. Quantitative results showed that perception by the origin of the tourist, references from others, the hospitality of tourism providers, media reports, natural resources and accessibility were the most dominating sources of brand association. To conclude, the study brand attitude was discovered as most effective in constructing a lasting association amid and beyond the COVID-19 pandemic. The study recommended innovative partnerships with global tourism agents in various target markets, intensive training of operators and employees in customer care, refurbishing tourism facilities, maximizing E-friendly customer care systems, and maintaining original aesthetic nature.